(untitled) (Journal of Hama University, 2022)
Pulpotomy is one of the most common clinical procedures for treating pulp in decayed primary teeth. Formocresol is the most widely used material in pulpotomy.Recently, plants with biological properties have been more common, such as aloe vera, which has anti-inflammatory, antibiotic, analgesic properties. Aim: To compare the efficacy of aloe vera gel with formocrisole in primary teeth pulpotomy clinically and radiographically. The study sample included 21 healthy children (5-9 years), visiting pediatric dentistry department. Each child had primary canines or molars indicated for extraction as a part of orthodontic treatment. The study sample consisted of 44 primary teeth divided into two groups. Group I:included 21 primrary teeth in which aloe vera gel was used as a pulpotomy medicament, and a mixture of zinc oxide with aloe vera gel (zoav) as a basal filling. Group II:included 23 primary teeth in which formocresol was used for pulpotomy, and the (zoe) cement as a basal filling. Amalgam was used as a final restoration. Clinical and radiographic evaluation was performed after one, six and twelve months. The clinical and radiographic success percentage in the aloe vera gel group was 95.2% after one year of observation compared to 78.3% in the formocresol group. Conclusion: This study did not show significant clinical and radiographic differences between aloe vera gel and formocresol in pulpotomy on primary teeth.